2012
DOI: 10.1016/j.neuron.2012.10.039
|View full text |Cite
|
Sign up to set email alerts
|

Single Neuron Activity and Theta Modulation in Postrhinal Cortex during Visual Object Discrimination

Abstract: Postrhinal cortex, the rodent homolog of the primate parahippocampal cortex, processes spatial and contextual information. Our hypothesis of postrhinal function is that it serves to encode context, in part, by forming representations that link objects to places. We recorded postrhinal neuronal activity and local field potentials (LFPs) in rats trained on a two-choice, visual discrimination task. As predicted, a large proportion of postrhinal neurons signaled object-location conjunctions. In addition, postrhina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
107
1
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(119 citation statements)
references
References 85 publications
10
107
1
1
Order By: Relevance
“…However, the anatomical data can also be interpreted as indicating that the functional segregation in the EC-CA1-subiculum pathway is not absolute, as the convergent LEC + MEC derived information from CA3 is passed onto all subregions of CA1. In addition, LEC and MEC are reciprocally connected (Dolorfo and Amaral 1998a), further supporting interactions between these pathways (Furtak et al 2012;Hunsaker et al 2013). …”
Section: Organization Of Connections In the Hippocampal Formationmentioning
confidence: 74%
“…However, the anatomical data can also be interpreted as indicating that the functional segregation in the EC-CA1-subiculum pathway is not absolute, as the convergent LEC + MEC derived information from CA3 is passed onto all subregions of CA1. In addition, LEC and MEC are reciprocally connected (Dolorfo and Amaral 1998a), further supporting interactions between these pathways (Furtak et al 2012;Hunsaker et al 2013). …”
Section: Organization Of Connections In the Hippocampal Formationmentioning
confidence: 74%
“…Similarly, LEC lesions primarily caused non-spatial deficits, but there were weak but significant spatial deficits. Physiologically, one synapse upstream from the entorhinal cortex, Furtak et al [40] showed that single units in the postrhinal cortex have both spatial and non-spatial correlates. Deshmukh & Knierim [35] demonstrated that a small but significant number of LEC cells (but not perirhinal cells; [41]) showed spatial firing that strongly resembled hippocampal place fields when there were objects present in the environment.…”
Section: Complications With the Simple 'What Versusmentioning
confidence: 99%
“…Whether information regarding the distal and proximal framework is provided to postsynaptic targets in the parietal cortex by anterior and lateral thalamic outflow, respectively, is unknown, but remains a major possibility given the strong connectivity between these three regions (Wilber et al, 2015). With respect to the postrhinal cortex, recent work has shown that neurons within this region respond to proximal stimuli and local contextual cues (Furtak et al, 2012). It has been recently suggested that the lateral thalamus, through its dense projections, likely plays a role in visual information processing by postrhinal neurons .…”
Section: Summary Conclusion and Unanswered Questionsmentioning
confidence: 99%